2019
DOI: 10.1007/s13201-019-0929-5
|View full text |Cite
|
Sign up to set email alerts
|

Potentiality of waste human hair towards removal of chromium(VI) from solution: kinetic and equilibrium studies

Abstract: Industrial and agricultural activities discharges huge amount of hazardous pollutants that lead to massive environmental pollution and health hazards. Keratin is a fascinating protein and useful biopolymer, which is usually found in wool, human hair, nails, feathers, etc. The present research deals with the potentiality of human hair towards removal of hexavalent chromium from aqueous solution through batch mode. The adsorbent was characterized by pH ZPC and SEM study. The Cr(VI) adsorption was studied with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…We found that the alkaline environment of the solution and NaOH modified hairs increased the adsorption of metals to soil and keratin fibers. Our findings are similar to [52,[60][61][62].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that the alkaline environment of the solution and NaOH modified hairs increased the adsorption of metals to soil and keratin fibers. Our findings are similar to [52,[60][61][62].…”
Section: Discussionsupporting
confidence: 92%
“…Hairs, as keratin-based adsorbents, are reported to reduce the concentration of HMs in both soil and water [7,52,[58][59][60][61][62]. There are two main mechanisms called physiosorption and chemisorption through which keratin material can remove HMs from air and solution.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of the adsorbent shows excellent performance toward significant Cr(VI) removal efficiency as well as adsorption capacity. Very recently, Mondal et al (2019b, c;Mondal and Basu 2019) reported that Cr(VI) can be removed by using mosambi peel, chicken feather and human hair. Therefore, more new materials should be developed so that effective Cr(VI) removal can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…The two main oxidation states of chromium are available in liquid medium; one is Cr(III) and other is Cr(VI). Moreover, out of these two oxidation state, Cr(VI) is thermodynamically more stable and highly mobile than Cr(III) (Mondal and Basu 2019;Ali et al 2016). Although the form of Cr(VI) is different in different pH medium as chromate (Cr 2 O 4 ), hydrochromate (HCrO 4 − ) or dichromate (AL-Othman et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many low-cost materials have been used by the earlier researchers for removal of Cr(VI) from aqueous solutions such as Aspergillus niger (Mondal et al 2017); banana peel (Ali et al 2016); potato peel (Mutongo et al 2014); human hair (Mondal and Basu 2019); groundnut hull (Owalude and Tella 2016); lychee peel (Rao et al 2012); chicken feather (Mondal et al 2019b), etc; however, none of the adsorbent showed high adsorption capacity. Therefore, a new easily available adsorbent should be developed for the fulfillment of the above objective.…”
Section: Introductionmentioning
confidence: 99%